Efficacy of Cholecalciferol In The Management Of Secondary Hyperparathyroidism In Hemodialysis Patients. - Asif, Naila; Rizwan, Muhammad; Rehman, Abdul; Durrani, Naureen (Pakistan Journal of Kidney Diseases, 2020)
Conventionally, secondary hyperparathyroidism (SHPT) has always been treated with active vitamin D analogues like calcitriol or calcidiol. The role of native vitamin D in end stage renal disease patients (ESRD) patients has always been questioned The aim of our study is to evaluate the role of native vitamin D in the form of cholecalciferol in the management of secondary hyperparathyroidism in patients on maintenance hemodialysis. METHODS: Forty-two maintenance hemodialysis patients were included with serum PTH > 300ng/L and vitamin D3 levels < 30ng/ml. Patients were followed for 3 months. Patients with vitamin D deficiency (vit D3 levels 5-15 ng/ml) were treated with Inj. Vitamin D3 600,000 I.U. monthly for 3 months. Patients with vitamin D insufficiency (16-30 ng/ml) were treated with 200,000 I.U. monthly for 3 months. RESULTS: Total 42 patients were taken with 16 male and 26 female patients. After treating patients with cholecalciferol, serum PTH levels improved significantly, with mean pre-treatment levels of 591.50±180.09, which had decreased to a mean post-treatment level of 317.80±199.05. Serum Vitamin D levels also improved significantly, with mean pre-treatment levels of 10.47±5.84, which increased to a mean post-treatment level of 33.33±15.31.Patients treated with cholecalciferol had no significant change in calcium and phosphorous levels. CONCLUSION: Native vitamin D in the form of cholecalciferol appears to be safe, effective and is inexpensive in the treatment of secondary hyperparathyroidism in patients on maintenance hemodialysis with no adverse effects.